Comparative Analysis of Pension Systems in Finland, Sweden and Poland – Conclusions and Challenges for Poland - OWCZARCZYK, ANNA; Albin, Jakub; Stanisławski, Mateusz (Management and Administration Journal, 2025)
Nowadays, there is increasing public discussion in Poland about the national pension system. People are wondering whether other countries can provide inspiration for pension system reform. The aim of this article is to present the functioning of pension systems in Finland, Sweden, and Poland, as well as to propose solutions that could potentially be utilized and implemented with appropriate adjustments in the Polish pension system. The research results are based on an analysis of literature, secondary sources, and statistical data. Proposals for changes to the Polish pension system were formulated after identifying the problems of the Polish system and analyzing selected Scandinavian pension systems. The reforms that have been proposed include equalizing the retirement age for both sexes, making pension contributions dependent on life expectancy, introducing pension contributions that go into an investment account, and reforming pension contributions for sole proprietorships. Based on the article, it can be concluded that reforms in the Polish pension system are certainly needed. Finding ideas for reform should not be difficult, as there is no need to invent a completely new system. It is enough to draw on solutions from highly developed European countries and implement them appropriately in Poland, of course taking into account the socio-economic conditions.